NILAI ETIKA BISNIS DALAM PEMBELAJARAN IPS - Gusti Noor Fanani (Universitas Lambung Mangkurat, 2019)
AbstractIn the people of South Kalimantan, there are sub-ethnic groups who are well-known as successful business people / entrepreneurs and can maintain their business in a relatively long time, namely Alabio. historically, Alabio have become traders/businessmen who are undoubtedly their trade characteristics. His success in commerce even began when there was a belief in